Como en un cuento de hadas, ¿o no? - Salas Alvarado, Jonnathan (2023)
Sofia, a good and innocent girl, meets the man who would be the love of her life. He creates for her a real fairy tale that suddenly takes an unexpected turn and is no longer what Sofia expected. This play takes us into the world of those idyllic relationships that, in the midst of a patriarchal society, end up not being what the woman expected. However, the play ends up leading us to an unexpected outcome.